Código de barras de DNA (DNA Barcode) de espécies de bagres (Ordem Siluriformes) de valor comercial da Amazônia brasileira - Batista, Elizangela Tavares (2017)
The Amazon basin presents the greatest ictic diversity in Brazil. Among the most abundant order in the region is the Order Siluriformes. The Order Siluriformes presents a great amount of species of fish commercialized in the Amazon. The molecular tool DNA barcode is used for the characterization of species in several types of animals, including in fish, through the use of a mitochondrial marker, Cytochrome Oxidase I region. The present work aimed to identify more species of Siluriformes Order. A total of 363 Cytochrome Oxidase subunit I (COI) gene sequences were obtained and analyzed, belonging to 33 species from 21 Brazilian Amazonian locations. The 33 species belonging to 22 genus 7 families of the Order Siluriformes, presented a total of 129 haplotypes. All sequences were submitted to the public databases (GenBank and Bold). About 96% were combined with sequences of said expected species, according to the morphological identification. The intraspecific average K2P genetic distance found was 0.003, and the interspecific genetic distance was 0,13. Most species had low interspecific genetic divergence values (<2%), but all could be correctly identified. The DNA bar code interacts between Classical and Molecular Taxonomy for an accurate identification of the species. The results of the present work demonstrated that as a taxonomic tool, the DNA Barcoding can be used for the molecular identification of fish of the Order Siluriformes. Keywords: Siluriformes; DNA Barcoding; Mitochondrial DNA; Cytochrome Oxidase I subunit.